2017
DOI: 10.1111/jep.12717
|View full text |Cite
|
Sign up to set email alerts
|

Real world evaluation of the smoking cessation services in the Rio de Janeiro municipality, Brazil

Abstract: Even though more than 20% of the patients did not attend the first group session, the access to treatment was high, and it was observed that the success rate of those who attended the fourth group session was more than 50%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Considering that it is less costly to help tobacco users to quit than to treat the tobaccorelated diseases, smoking cessation is one of the most relevant health interventions [7]. Studies have shown the effectiveness of pharmaceutical services for smoking cessation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Considering that it is less costly to help tobacco users to quit than to treat the tobaccorelated diseases, smoking cessation is one of the most relevant health interventions [7]. Studies have shown the effectiveness of pharmaceutical services for smoking cessation [8][9][10].…”
Section: Introductionmentioning
confidence: 99%